2019
DOI: 10.1103/physreve.100.023114
|View full text |Cite
|
Sign up to set email alerts
|

Electric fields enable tunable surfactant transport to microscale fluid interfaces

Abstract: The transport dynamics of oil-soluble surfactants to oil-water interfaces are quantified using a custom-built electrified capillary microtensiometer platform. Dynamic interfacial tension measurements reveal that surfactant transport is enhanced under a D.C. electric field, due to electromigration of charge carriers in the oil toward the interface. Notably, this enhancement can be precisely tuned by altering the field strength and temporal scheduling. For the first time, we demonstrate electric fields as a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…(d) Measured dynamic IFT showing that the IFT decays faster when the electric field is stronger. Reprinted figures with permission from ref . Copyright 2019 American Physical Society.…”
Section: Measurement Of Dynamic Interfacial Tensionmentioning
confidence: 99%
See 1 more Smart Citation
“…(d) Measured dynamic IFT showing that the IFT decays faster when the electric field is stronger. Reprinted figures with permission from ref . Copyright 2019 American Physical Society.…”
Section: Measurement Of Dynamic Interfacial Tensionmentioning
confidence: 99%
“…The dynamic IFT can then be extracted using eq with measured Δ P and R c , both as a function of time. Following the work by Alvarez et al, Sengupta et al , utilized this microtensiometer apparatus to further investigate the effect of electric fields on the surfactant transport to oil–water interfaces using a setup similar to that shown in Figure (c), in which the electric field is applied across the electrodes on the side of the cell. The dynamic IFT is measured with two different surfactants, in which they found that the transport of oil-phase surfactants is enhanced due to the electrophoresis of charge carriers (Figure (d)).…”
Section: Measurement Of Dynamic Interfacial Tensionmentioning
confidence: 99%
“…In the literature many experimental works [55,[81][82][83] show that the transport of bulk surfactant is nonlinearly coupled with drop curvature, surfactant physicochemical properties, and external flows. Analytical investigation on drop hydrodynamics with surfactant sorption kinetics is challenging due to the complex nonlinear coupling between surfactant diffusion, sorption kinetics, drop deformation and Maragoni stress.…”
Section: Discussionmentioning
confidence: 99%
“…Table I summarizes the existing theoretical and numerical investigations in the literature. In most of these studies [42][43][44][45][46][47][48][49][50][51]55], surfactants are assumed to be insoluble and the surface tension is described using either a linear relationship, or more realistically the Langmuir equation of state…”
Section: Fluidsmentioning
confidence: 99%
See 1 more Smart Citation